INDICATIONS AND INSERTION METHODS OF DOUBLE J URETERAL STENTING IN Dr. SOETOMO HOSPITAL, SURABAYA - Fathurrahman, Hasroni; Hakim, Lukman (Medicina Biomedica Journal, 2022)
Introduction Objectives : Double J ureteral stents (DJ stent) have become one of the most basic and valuable tools in the urological practice. Insertion of DJ stent provide direct drainage from the kidney to the bladder without the need for external diversion. The indications for insertion of stents into the urinary tract has expended significantly for oncology also non-oncology case. This study was designed to observe the indication and insertion metode of DJ ureteral stenting in Department of Urology, Medical faculty of Airlangga University dr. Soetomo Hospital, Surabaya, from January 2012 to December 2015.AIM: The purpose of this study was to determine the characteristics of patients with perirenal abscess and their management.Materials and Methods : Retrospective-Descriptive Study was conducted at Department of Urology, Medical faculty of Airlangga University dr. Soetomo Hospital, Surabaya from January 2012 to December 2015 with total number of 836 patients who underwent DJ ureteral stenting. Additional analysis was done for factors affecting indication, age, sex, and insertion methods.Results : Majority of the patients 829 (99,2%) were adults between 17 to 81 years with mean age 47 years old with male to female ratio was. 1:1,3. Majority of insertion methods was with endourology 748 (89 %) and open surgical 88 (11 %), The most common indication for DJ ureteral stenting was urinary tract stone disease (kidney: 130, ureter: 315, kidney and ureter: 80) total 525 patients(63 %), and followed by oncology case 254 patients (30 %), stenosis (ureter: 19, UVJ: 3, UPJ: 16) total 38 patients (5 %) dan neglected DJ stent 19 patients(2 %). The most common cause of DJ ureteral stenting for male was urinary tract stone disease 201 patients (38,2 %), and the most common cause of DJ ureteral stenting for female was oncology case 37 patients (93,4 %).Conclusion : Majority of the patients that performed DJ ureteral stenting 829 (99,2%) were adults with male to female ratio was. 1:1,3. Majority of insertion methods of DJ stents was with endourology. The most common indication for DJ ureteral stenting was urinary tract stone disease and followed by oncology case.